Age-depth data and chemistry from a shallow firn core collected in Southwest Greenland, 2018 - Rennermalm, Asa; Osterberg, Erich; Hock, Regine; Xiao, Jing; Covi, Federico; Leidman, Sasha; MacFerrin, Michael; Muthyala, Rohi; Tedesco, Marco (NSF Arctic Data Center, 2021)
This dataset contains age-depth information for one 16 meter (m) shallow core collected in Southwest Greenland in 2018. The dataset also includes chemistry and isotope measurements. The dating was done by matching up the isotope measurements with previous data (see methods). Density and ice layer in the core was measured in the field and is published in Arctic Data Center dataset (doi:10.18739/A2VH5CK05). During transportation from the field to the laboratory parts of the core were compacted and or damaged resulting in crumbled pieces. Due to these damages to parts of the core, the total thickness of the laboratory-measured core was 1.8 m shorter than the total thickness measured in the field. The depths reported in this dataset have been adjusted to match the depth scale of the stratigraphy data set. Metadata about the core Core length 18 m Collection year: 2018 Site name according to Rennermalm et al., 2021, J. Glaciol.: Core 8 Dates the core was drilled: 19-20 May 2018 Site latitude in degrees north: 66.98269 Site latitude in degrees east (i.e. negative values is degrees west): -45.04649 Elevation recorded on handheld GPS in the field: 2266 m a.s.l. Elevation derived from Polar Geospatial Center's ArcticDEM adjusted to mean sea level, see more info in Rennermalm et al. 2021: 2254 m a.s.l. Associated dataset: Density and ice layers for Core 8 is found at the Arctic Data Center dataset (doi:10.18739/A2VH5CK05). References: Rennermalm, Å. K., Hock, R., Covi, F., Xiao, J., Corti, G., Kingslake, J., Leidman S. L., Miege, C., MacFerrin, M., Machguth, H., Osterberg, E., Kameda, T., McConnell. J. 2021. Shallow firn cores 1989 - 2019 in southwest Greenland’s percolation zone reveal decreasing density and ice layer volume after 2012. Journal of Glaciology, 1-12, https://doi.org/10.1017/jog.2021.102